2010
DOI: 10.1016/j.schres.2010.05.012
|View full text |Cite
|
Sign up to set email alerts
|

High dose D-serine in the treatment of schizophrenia

Abstract: Background D-serine is an allosteric modulator of the brain N-methyl-D-aspartate (NMDA) receptor and a potential novel treatment of schizophrenia. Double-blind studies have been performed at 30 mg/kg/day (~2 g/day) with encouraging results, but no formal dose escalation studies have been performed. We describe the first evaluation of the efficacy and safety of D-serine at doses >30 mg/kg/day; a 4-week, open-label trial of adjunctive D-serine (30, 60 or 120 mg/kg/day). Methods 42 antipsychotic-stabilized pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
177
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(186 citation statements)
references
References 19 publications
2
177
2
4
Order By: Relevance
“…Считают, что особенно оправданно использование D-серина, который обладает высоким сродством к глицино-вому сайту NMDA-рецепторов и легко проникает через ге-матоэнцефалический барьер. По данным некоторых иссле-дователей [86,87], добавление D-серина к обычной нейро-лептической терапии существенно повышает ее эффектив-ность, особенно в отношении негативных симптомов.…”
Section: дисфунция астроцитов при шизофрении как перспективная мишеньunclassified
“…Считают, что особенно оправданно использование D-серина, который обладает высоким сродством к глицино-вому сайту NMDA-рецепторов и легко проникает через ге-матоэнцефалический барьер. По данным некоторых иссле-дователей [86,87], добавление D-серина к обычной нейро-лептической терапии существенно повышает ее эффектив-ность, особенно в отношении негативных симптомов.…”
Section: дисфунция астроцитов при шизофрении как перспективная мишеньunclassified
“…A number of clinical studies [62,65,[88][89][90] have demonstrated that adjuvant DSR (30-120 mg/kg/day) added to ongoing treatment with non-clozapine antipsychotics results in significant symptom improvements in chronic schizophrenia patients. The most significant changes were registered in the negative symptom cluster ( Figure 2).…”
Section: Schizophreniamentioning
confidence: 99%
“…Two schizophrenia treatment issues stemming from these findings are the potential use of DSR for improving cognition and as stand-alone pharmacotherapy in this disorder. In a preliminary four week open-label study [65], it was shown that high dose DSR (≥60 mg/kg/day) improves neurocognitive functions as measured by the Measurement and Treatment Research to Improve Cognition in Schizophrenia (MATRICS) battery. An additional controlled pilot investigation [93] compared the effectiveness of DSR (3 g/day) versus high-dose olanzapine (30 mg/day) as antipsychotic monotherapy in 18 treatment-resistant schizophrenia patients.…”
Section: Schizophreniamentioning
confidence: 99%
“…102) Because glycine modulates NMDA receptor function, the glycine agonist D-serine is under investigation and has shown positive preliminary results, while, inhibitors of glycine reuptake are also being studied. 105) Studies of GABAergic agents, such as MK-0777-a GABA (A) α2/α3 partial agonist have produced conflicting results thus far. 106) Modafinil and d-amphetamine have promising pro-cognitive effects, though their clinical use for this purpose in schizophrenia patients remains to be established.…”
Section: Synergy With Pharmacological Treatmentsmentioning
confidence: 99%